Зарубіжний досвід використання осушених земель для України - Третяк, Н.А.; Третяк, Р.А.; Шашула, Л.О. (Економіка природокористування і охорони довкілля, 2017)
Висвітлено, що на тлі глобальних проблем людства перед країнами в цілому стоїть завдання раціонального та ефективного використання і збереження ресурсного потенціалу. Зазначено, що в сучасних умовах господарювання, зокрема на осушених землях, це безпосередньо залежить від рівня наукового забезпечення та чинної законодавчо-нормативної бази.
З’ясовано, що правовий аспект регулювання економічних й екологічних відносин організації використання осушених земель в Україні оцінюється як незадовільний. Обґрунтовано нагальну необхідність удосконалення відповідного законодавства та організаційного механізму з урахуванням міжнародного досвіду та апроксимацій директив Європейського Союзу.
Проаналізовано стан осушених земель в Україні та зарубіжних державах, а також інституційного забезпечення організації їх ефективного використання. Запропоновано заходи, спрямовані на раціональне залучення наявного потенціалу цієї категорії земель та його подальшого розвитку. Deals that recently in the world in terms of global challenges, the country as a whole, the challenge of rational and efficient use and conservation of their resource potential. It is noted that in the current economic conditions the efficient use of land reclaimed in particular, depends on scientific support and legal and regulatory framework.
It was established that the existing legal framework for the regulation of economic relations and environmental organizations use reclaimed land in Ukraine is rated as unsatisfactory. Revealed the need for immediate improvement of the legislation on the organization of effective use of reclaimed land and the institutional mechanism with European experience and approximations of the European Union.
We analyzed the world experience of using of reclaimed lands. The state of drained land in Ukraine as well as institutional support of the organization of their effective use are analyzed. The problems of institutional support of organizations effective use and conservation of drained lands of Ukraine are presented. There were established the ways of reclaimed land use according to the world experience. The ways for overcome them in a new land relations are proposed. There were grounded measures aimed at ensuring to restore the effective use of existing potential drained land and its further development.